Sedative and cardiorespiratory effects of acepromazine or atropine given before dexmedetomidine in dogs - Alvaides, R. K. [UNESP]; Teixeira Neto, F. J. [UNESP]; Aguiar, A. J.A. [UNESP]; Campagnol, D. [UNESP]; Steagall, P. V.M. [UNESP] (Wiley, 2008)
To test the hypothesis that acepromazine could potentiate the sedative actions and attenuate the pressor response induced by dexmedetomidine, the effects of acepromazine or atropine were compared in six healthy adult dogs treated with this α2-agonist. In a randomised block design, the dogs received intravenous doses of either physiological saline, 0-05 mg/kg acepromazine or 0-04 mg/kg atropine, 15 minutes before an intravenous dose of 5 ug/kg dexmedetomidine. The dogs' heart rate was reduced by 50 to 63 per cent from baseline and their mean arterial blood pressure was increased transiently from baseline for 20 minutes after the dexmedetomidine. Atropine prevented the α2-agonist-induced bradycardia and increased the severity and duration of the hypertension, but acepromazine did not substantially modify the cardiovascular effects of the α2-agonist, except for a slight reduction in the magnitude and duration of its pressor effects. The dexmedetomidine induced moderate to intense sedation in all the treatments, but the dogs' sedation scores did not differ among treatments. The combination of acepromazine with dexmedetomidine had no obvious advantages in comparison with dexmedetomidine alone, but the administration of atropine before dexmedetomidine is contraindicated because of a severe hypertensive response.